REALITAS SOSIAL DALAM VIDEO PERTUNJUKAN “UBRUG” BERJUDUL “HALIWU” - Zanuar Eko Rahayu (BBPPMPV Seni dan Budaya Yogyakarta, 2023)
The purpose of the study is to find out and to describe social reality in the video of “ubrug”performance with the story of